Peer Coaching as a Strategy for Teachers’ Professional Development - धमला Dhamala बद्रीप्रसाद Badri Prasad (Okhaldhunga Journal, 2024)
This study explores the English language teachers’ practices of peer coaching as a strategy for their professional development. Peer coaching is a strategy where one or more teachers from a partnership with one another for the purpose of collaboration and it also provides professional development. For this study, a sample of forty secondary and lower-secondary level teachers of English were selected from twenty schools in the Okhaldhunga district using purposive sampling procedures. Two English teachers from twenty schools were selected. A questionnaire was used that also included open-ended questions. Fifteen closed - ended and six open – ended questionnaires were used to collect required data. Teachers strongly agreed that peer coaching reduces the sense of isolation. They viewed that peer coaching is a procedure in which two teachers collaborate to help one or both to improve English language problems.